Rivalry and performance: A systematic review and meta-analysis. (August 2022) - Milstein, Nir; Striet, Yarin; Lavidor, Michal; Anaki, David; Gordon, Ilanit
Rivalry, a relational competition, is known to increase motivation and performance. However, a systematic review and meta-analysis that examines the effect sizes is lacking. Further, most research on this topic has not considered the type of rivalry (individual versus collective) and the research field as potential moderators. We conducted a wide-scale search, looking for rivalry and performance studies, which yielded 22 papers (k = 35) with 27, 771 observations that were systematically reviewed. Eighteen papers (k = 28) were eligible for a further meta-analysis, including a total of 26, 215 observations. The systematic review indicated that rivalry is usually positively related to performance. Results of the meta-analysis revealed that this effect is significant and that the relationship between rivalry and performance is more robust for individual rivalry compared to group rivalry. Further analyses indicated that for group rivalry, correlations are positive and significant only in the domains of sports and donation-raising.Plain Text Abstract Rivalry is a unique and common type of competition in which the competing parties have longstanding relationships. When rivalry is present, the competing actors have an increased desire to win and invest extra effort into the competition, leading to enhanced performance. However, an integration of studies that examine the effects of rivalry, as a relational competition, is lacking. Here, we scanned studies from diverse research fields that claimed to measure rivalry and actor's performance. We considered only research that specifically measured rivalry as a relational competition and its association with performance. We systematically reviewed eligible studies and found that, generally, rivalry is positively related to performance. We then performed a meta-analysis that confirmed that this relationship is statistically significant. We further found that this relationship is more robust for rivalries in the context of individuals compared to groups. The association between rivalry and performance is most prominent in certain domains, such as sports rivalry. These findings can guide scholars in designing research on rivalry. Specifically, considering the various effect sizes found here in different contexts of rivalry will allow researchers to plan for more appropriate sample sizes designed to reveal the relationship between rivalry and performance in a targeted domain. Further, these results can inform managers about the effects of rivalries in or between their organizations, distinguishing among the different contexts of rivalries and their specific outcomes.